2021
DOI: 10.1021/acs.iecr.1c03495
|View full text |Cite
|
Sign up to set email alerts
|

Study on High-Efficiency Photocatalytic Degradation of Oxytetracycline Based on a Spiral Microchannel Reactor

Abstract: In this work, a spiral microchannel reactor was used to study the photocatalytic degradation process of oxytetracycline (OTC) in a titanium dioxide (TiO2) slurry system. The influence of parameters such as residence time, TiO2 dosage, OTC concentration, light intensity, and concentration of added ions (NO3 –, SO4 2–, Ca2+, Fe3+) on OTC removal was systematically investigated, and the degradation stability of OTC in the microreactor was evaluated. The results show that under the best experimental conditions, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The apparent reaction rate constant ( K app ) was obtained from the experimental data by fitting a pseudo-first-order kinetic model as shown in eq : ln nobreak0em.25em⁡ C t C 0 = K app t …”
Section: Methodsmentioning
confidence: 99%
“…The apparent reaction rate constant ( K app ) was obtained from the experimental data by fitting a pseudo-first-order kinetic model as shown in eq : ln nobreak0em.25em⁡ C t C 0 = K app t …”
Section: Methodsmentioning
confidence: 99%
“…60 The inhibition of the degradation kinetics of CIP was probably ascribed to the adsorption of cations that reduced the active sites on the surface of the photocatalyst 61,62 and the formation of refractory complexes produced by interaction of cations and CIP. [63][64][65] In addition, Mg 2+ and Ca 2+ can also inhibit the photocatalytic degradation process by filtering the radiation 66 and by interacting with the catalyst surface to quench photoelectrons. 67 It has been observed that NO 3 − , NO 2 − , and Cl − typically reacted with ROSs to generate reactive nitrogenous radicals (RNS) and reactive chlorinated radicals (RCS) such as ˙NO 3 , ˙NO 2 , and ˙Cl (eqn ( 13)-( 16)).…”
Section: 24mentioning
confidence: 99%
“…A large variety of harmful dyes have been found in toxic wastewater effluents from various industries including textile and pharmaceutical sectors. Reactive dyes are basically classified by the presence of azo chromophores, which are considered toxic and mutagenic to living organisms. A very small amount of the reactive red azo dye in water is visible and undesirable . Thus, it is a matter of high concern to find out a cost-effective technology for the treatment of water containing this toxic dye. , The oxytetracycline (OTC) antibiotic is extensively used in humans for the treatment of bacterial infectious diseases. However, this drug causes a serious problem to the environment. After OTC is metabolized in the body, there is a chance that the toxic byproducts could enter the natural water. , This causes damage to the ecosystem and human health.…”
Section: Introductionmentioning
confidence: 99%